1999
DOI: 10.1046/j.1537-2995.1999.39399219284.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of red cell aggregability and shape during blood storage

Abstract: Because blood transfusion is routinely given to patients with normal or high fibrinogen level, the transfusion of stored red cells has the potential to induce increased aggregation in vivo, depending on the storage period. This should be taken into account when blood transfusion is considered, particularly for patients with microcirculatory disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
2
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(138 citation statements)
references
References 22 publications
4
125
2
4
Order By: Relevance
“…6,[16][17][18] The coadministration of toxic substances that accumulated in the storage supernatant including microparticles, lipophosphatidylcholines, cytokines, free hemoglobin, and iron may promote inflammatory response and oxidative stress and contribute to organ tissue dysfunction in transfused patients. [19][20][21][22][23][24] AKI is a common adverse event after PCI and is associated with increased morbidity and mortality and health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…6,[16][17][18] The coadministration of toxic substances that accumulated in the storage supernatant including microparticles, lipophosphatidylcholines, cytokines, free hemoglobin, and iron may promote inflammatory response and oxidative stress and contribute to organ tissue dysfunction in transfused patients. [19][20][21][22][23][24] AKI is a common adverse event after PCI and is associated with increased morbidity and mortality and health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…19 Transfusion of stored RBCs also has been shown to induce tissue hypoxia in rodents. 20,21 Increased red cell aggregability 22 and rigidity, 23 the diminished microvascular autoregulatory abilities of stored red cells, 20,24 and the accumulation of potentially toxic microparticles, 25 lipophosphatidylcholines, 26 or proinflammatory cytokines 27 in the storage supernatant may all contribute to tissue hypoxia and organ dysfunction in transfused patients. Alternatively, systemic inflammation, a feature of the response to transfusion of nonleukodepleted red cells, 27 is implicated in atherosclerotic plaque rupture, stroke, and acute coronary syndromes.…”
Section: Findings In the Context Of The Literaturementioning
confidence: 99%
“…16,26,32,42,43 Evidence also indicates that CPB adversely affects RBC structure and function, [23][24][25] and one study has shown functional changes in salvaged autologous RBCs tested in vitro, but not in blood sampled from patients after salvaged blood transfusion. 44 In our study, we found that neither salvaged RBCs nor CPB, when studied in combination, had a detrimental effect on RBC deformability.…”
Section: Discussionmentioning
confidence: 99%